catena-Poly[[triphenyltin(IV)]-μ-5-amino-2-nitrobenzoato-κ(2) O (1):O (1′)] - Win, Yip-Foo (International Union of Crystallography, 2011)
The title compound, [Sn(C(6)H(5))(3)(C(7)H(5)N(2)O(4))](n), forms polymeric chains along [010]. The Sn(IV) ion is five-coordinated in a distorted trigonal–bipyramidal geometry by two monodentate carboxylate groups and three phenyl rings. The axial sites are occupied by the O atoms of two symmetry-related carboxylate groups [O—Sn—O = 170.88 (3)°]. The benzene ring of the 5-amino-2-nitrobenzoate ligand forms dihedral angles of 82.92 (6), 81.10 (6) and 83.54 (6)° with respect to the three phenyl rings. In the crystal, the chains are linked by intermolecular N—H⋯O and weak C—H⋯O interactions into a three-dimensional network. The crystal structure is further stabilized by weak intermolecular C—H⋯π interactions.